2018
DOI: 10.3389/fmicb.2018.02612
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendment Under Increasing Agricultural Intensification: Effects on Soil Bacterial Communities and Plant Productivity

Abstract: The soil microbiome is a complex living network that plays essential roles in agricultural systems, regardless of the level of intensification. However, the effects of agricultural management on the soil microbiome and the association with plant productivity remain largely unclear. Here, we studied the responses of three soil systems displaying distinct levels of agriculture intensiveness (i.e., natural, organic, and conventional soil management regimes) to experimentally manipulated organic farming amendments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Fungal and bacterial communities in the soil were structured by soil type -but not by agricultural system -which is in agreement with the findings of Fierer and Jackson (2006) and Fierer (2017) who have shown that the edaphic properties inherent to particular soil types are the principle drivers of soil microbial composition. Previous studies found differences in organic and conventional practices, namely that the addition of organic fertilizers only instead of the addition of artificial fertilizers led to significant differences of microbial composition mainly in arable soils, of fungi (Lalande et al, 2005;Ghimire et al, 2014) and also of bacteria (Mas-Carrió et al, 2018) but that the effect of grassland is dominating the effect of system (Rutgers et al, 2008;Deru et al, 2018). The fermentation process that silage undergoes that selects for lactic acid bacteria (McDonald, 1981) most likely determined its microbial composition, as observed by the high relative abundance of Lactobacillaceae.…”
Section: Residualmentioning
confidence: 99%
“…Fungal and bacterial communities in the soil were structured by soil type -but not by agricultural system -which is in agreement with the findings of Fierer and Jackson (2006) and Fierer (2017) who have shown that the edaphic properties inherent to particular soil types are the principle drivers of soil microbial composition. Previous studies found differences in organic and conventional practices, namely that the addition of organic fertilizers only instead of the addition of artificial fertilizers led to significant differences of microbial composition mainly in arable soils, of fungi (Lalande et al, 2005;Ghimire et al, 2014) and also of bacteria (Mas-Carrió et al, 2018) but that the effect of grassland is dominating the effect of system (Rutgers et al, 2008;Deru et al, 2018). The fermentation process that silage undergoes that selects for lactic acid bacteria (McDonald, 1981) most likely determined its microbial composition, as observed by the high relative abundance of Lactobacillaceae.…”
Section: Residualmentioning
confidence: 99%
“…Compost or vermicompost produced from various organic wastes is an essential agricultural supplement because of their beneficial effects on diverse properties of soil (Zandvakili et al 2019). These organic amendments are reported to enhance the growth of plants by providing essential nutrients, improving beneficial microorganisms, and managing harmful pests and diseases (Stewart-Wade 2020), and may have a long-term effect on agroecosystem productivity and sustainability (Mas-Carrió et al 2018;Domínguez et al 2019). Both composts and vermicomposts are used for the growth and development of crops; however, due to some negative aspects of compost such as higher electrical conductivity, existence of more pathogens, low nutrient concentrations, and higher phytotoxicity (García-Gómez et al 2002;Bloem et al 2017;Joshi et al 2020), vermicompost is preferred for plant growth by most of the consumers.…”
Section: Superiority Of Vermicompost Over Compostmentioning
confidence: 99%
“…The structure of soil microorganism communities is particularly essential for soil ecosystems to function at maximum efficiency [23][24][25], where soils characterized by a high abundance and diversity of microorganisms are considered to provide the needed ecosystem services [26,27]. Studies conducted by many scientists have identified increasing soil functional diversity and microbiome complexity as one of the mechanisms by which organic amendments contribute to soil health [28][29][30][31][32]. However, it is often unclear whether organic amendments have consistent or long-term effects on soil microbial communities, restricting our capacity to foresee how soil conditioners may affect different types of soils' microbial populations.…”
Section: Introductionmentioning
confidence: 99%